EFEKTIVITAS EDUKASI ANTENATAL TERHADAP KETAKUTAN DAN EFIKASI DIRI PERSALINAN PADA PRIMIPARA: SYSTEMATIC REVIEW - Syamsuriati, Syamsuriati; Rachmawati, Imami Nur; Kurniawati, Wiwit (Media Penelitian dan Pengembangan Kesehatan, 2024)
Fear of giving birth due to lack of knowledge causes a decrease in primigravida mothers' confidence in their ability to undergo childbirth. Decreased self-efficacy in childbirth can cause birth complications such as prolonged labor, fatigue and weakness in the mother, which results in the mother's failure to undergo a natural birth. Antenatal education is an appropriate alternative to increase mothers' knowledge of the birth process. The aim of the research was to examine the effectiveness of antenatal education in reducing fear of childbirth and increasing childbirth self-efficacy in primiparous mothers. The structure of this research is a detailed analysis using the PRISMA flow diagram. Researchers applied the PICO method and searched for articles in English published between 2018 and 2023. Some of the databases used included Proquest, PUBMED, Sage Journal, Springer Link, Science Direct, EBSCO, Plos One and Taylor & Francis. Article quality assessment using JBI Critical Appraisal Tools for RCT. Seven articles were identified and analyzed, all articles used a Randomized Controlled Trial design. The research sample numbered 56 to 182, consisting of primiparas in the age range 18-32 years with a gestational age of <34 weeks and was conducted in Saudi Arabia, Turkey, Iran and China. From the literature search, in general it can be concluded that antenatal education provided to primiparous mothers is effective in reducing fear of childbirth and increasing self-efficacy in childbirth.